Adapting to Climate Change: Threat Experience, Cognition and Protection Motivation - Susann Adloff (ZBW - Leibniz Information Centre for Economics, 2021)
Climatic changes largely unfold by means of two types of events: extreme events and gradual long-term changes. This paper highlights how the difference in occurrence probability and (marginal) impact between the two event types leads to structural differences in cognitive processing of event experiences. Building upon insights on imperfect memory and optimization behaviour under (inter-temporal) uncertainty, I theoretically argue how differences are likely to occur at the level of event awareness, expectation formation and adaptation motivation. This postulation is empirically corroborated using data on the willingness to protect against coastal hazards from a sample population that is simultaneously exposed to sea level rise and coastal flooding. For both event types, event awareness is found to be heterogeneous across individuals with comparable actual experience levels. These variations in awareness are able to explain variations in expectations and protection motivation, however, only in the case of sea level rise. Instead, in case of coastal flooding, protection motivation is found to be sensitive to variations in expectations which are decoupled from heterogeneities in event awareness. These findings outline two structurally different cognitive routes underlying protection motivation. They indicates that the effectiveness of policy approaches to overcome climate change adaptation thresholds is likely to depend on the particulars of the threat type and calls for more nuanced future research.
Keywords: Q54; D91; 330